TPLATE Recruitment Reveals Endocytic Dynamics at Sites of Symbiotic Interface Assembly in Arbuscular Mycorrhizal Interactions - Russo, Giulia (Front Plant Sci, 2019)
Introduction: Arbuscular mycorrhizal (AM) symbiosis between soil fungi and the majority of plants is based on a mutualistic exchange of organic and inorganic nutrients. This takes place inside root cortical cells that harbor an arbuscule: a highly branched intracellular fungal hypha enveloped by an extension of the host cell membrane—the perifungal membrane—which outlines a specialized symbiotic interface compartment. The perifungal membrane develops around each intracellular hypha as the symbiotic fungus proceeds across the root tissues; its biogenesis is the result of an extensive exocytic process and shows a few similarities with cell plate insertion which occurs at the end of somatic cytokinesis. Materials and Methods: We here analyzed the subcellular localization of a GFP fusion with TPLATE, a subunit of the endocytic TPLATE complex (TPC), a central actor in plant clathrin-mediated endocytosis with a role in cell plate anchoring with the parental plasma membrane. Results: Our observations demonstrate that Daucus carota and Medicago truncatula root organ cultures expressing a 35S::AtTPLATE-GFP construct accumulate strong fluorescent green signal at sites of symbiotic interface construction, along recently formed perifungal membranes and at sites of cell-to-cell hyphal passage between adjacent cortical cells, where the perifungal membrane fuses with the plasmalemma. Discussion: Our results strongly suggest that TPC-mediated endocytic processes are active during perifungal membrane interface biogenesis—alongside exocytic transport. This novel conclusion, which might be correlated to the accumulation of late endosomes in the vicinity of the developing interface, hints at the involvement of TPC-dependent membrane remodeling during the intracellular accommodation of AM fungi.